1984
DOI: 10.4206/bosque.1984.v5n2-04
|View full text |Cite
|
Sign up to set email alerts
|

Estructura Y Dinamica De Bosques Del Tipo Forestal Siempreverde en Un Sector De Chiloe Insular

Abstract: A study on structural and dynamic cha racterization of the forest was carried out in an area of the evergreen forest type lo cated in the neighbourhoods of Chepu, in the Isla Grande de Chiloé. Four stands on undisturbed forests were selected and 54 x 72 m plots were established in each one of them. Data for drawing vertical profi les, for crown classification, stand tables, diameter distribution diagrams, understo rey composition and structure and for spatial distribution of the species using the Morisita Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
12

Year Published

1988
1988
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 11 publications
0
41
0
12
Order By: Relevance
“…Previous studies in the forests of central Chiloé have reported statistically significant relationships between diameter and age for several of the main species in this study [8,11,16]. Consequently, it is possible to interpret the dynamics and successional stage of these forests based on their diameter structure and regeneration, especially in this study where variations in structure and composition are not the result of environment or site, which is homogeneous in the study area.…”
Section: Forest Groups In the Evergreen Forests Of Southern Chiloémentioning
confidence: 83%
See 3 more Smart Citations
“…Previous studies in the forests of central Chiloé have reported statistically significant relationships between diameter and age for several of the main species in this study [8,11,16]. Consequently, it is possible to interpret the dynamics and successional stage of these forests based on their diameter structure and regeneration, especially in this study where variations in structure and composition are not the result of environment or site, which is homogeneous in the study area.…”
Section: Forest Groups In the Evergreen Forests Of Southern Chiloémentioning
confidence: 83%
“…UPGMA is a consistent agglomerative clustering algorithm in which between-group dissimilarities are calculated as the average of all possible pairs of members of each group [28]. To perform the cluster analysis we included all the tree species from this study and those reported by other authors for evergreen forests of the North-Patagonian archipelago [8][9][10]13,[16][17][18] (see list of tree species in supplementary Table S1). This approach could be influenced by the different sampling effort between studies, but since we focused the analysis only on tree species, this should not be a problem.…”
Section: Experimental Design and Statistical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…For soil sampling, we established a randomized complete design with three replicates (plots) randomly distributed in each tree cover level. All plots had a size of 50 × 50 m (following the recommendations of Donoso et al, 1984), a slope ranging from 10% to 15%, a uniform aspect, and were located at similar elevations (1200 m a.s.l.) (Table 1).…”
Section: Experimental Design and Samplingmentioning
confidence: 99%